2021
DOI: 10.1002/pc.26015
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of mixed mode fracture toughness of glass fiber/epoxy laminates with sea water absorption

Abstract: Degradation of composites properties with water absorption is a severe threat to its application in marine structures and humid environments. Real life composite structures often work under mixed mode loading. In this paper, Glass fiber composite has been investigated for the influence of sea water aging on the fracture toughness under mixed mode loading. Glass fiber/epoxy specimens were immersed for 21 and 35 days in sea water. Controlled mixed mode loading was applied using mixed mode bending fixture. Dry an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…[4][5][6] The integrity of the composites can be negatively affected in the marine environment. Studies have shown that the impact performance, 7 bending strength, 8 tensile strength, 9 fracture toughness, 10 and other mechanical properties of laminated and woven composites subjected to marine environments can be reduced. The crack initiation and propagation speed of the composites increase under fatigue load after seawater immersion, thus decreasing their fatigue life.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] The integrity of the composites can be negatively affected in the marine environment. Studies have shown that the impact performance, 7 bending strength, 8 tensile strength, 9 fracture toughness, 10 and other mechanical properties of laminated and woven composites subjected to marine environments can be reduced. The crack initiation and propagation speed of the composites increase under fatigue load after seawater immersion, thus decreasing their fatigue life.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors that affect absorption are contact time, temperature, fiber volume fraction, packing and arrangement, and crosslink density for the thermoset matrices. The absorption of fluids, including fuels and water, by the composites can deteriorate their mechanical properties, including moduli, strengths, and interlaminar fracture toughness 11–41 …”
Section: Introductionmentioning
confidence: 99%
“…The absorbed moisture severely affects the fiber/matrix interface and as a result, the mechanical properties of composites degrades over the service life. [1][2][3][4][5][6][7][8] For example, the moisture absorption was found to decrease the tensile and compression strength of carbon fiber/epoxy composites by 12% and 47%, respectively. [7] It was also found to decrease the fracture toughness and flexural strength of glass fiber/epoxy composites by 49% and 43%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[7] It was also found to decrease the fracture toughness and flexural strength of glass fiber/epoxy composites by 49% and 43%, respectively. [5,8] The reductions in mechanical properties were attributed to the degradation of fiber/matrix interface due to moisture absorption. To overcome the issues related to moisture absorption, techniques like modification of matrix resin, [9][10][11] functionalization of fibers, [12,13] and surface modification of fibers [14,15] were adopted.…”
Section: Introductionmentioning
confidence: 99%